BUDIDAYA TANAMAN TANJUNG (Mimusops elengi L.) DALAM UPAYA PELESTARIAN LINGKUNGAN DI KELURAHAN NGADE - Aqshan Shadikin; Andy Kurniawan (UNIVERSITAS KHAIRUN, 2018)
The process of development and development of a city runs very fast, so that if this process isnot balanced with environmental management is feared will lead to declining urbanenvironmental quality. Urban development has negative consequences on several aspects,including environmental aspects. At this time it has been recognized that the urban climate hasdifferent characteristics with the climate of the surrounding area that still has enough naturalelements. The cultivation of Tanjung trees provides benefits to the environment such asmicroclimate control, water catchment areas, maintaining the balance and physical harmony ofthe city, supporting conservation and biodiversity. Based on the evaluation result of thededication team, it can be seen that the trainees have been able to practice the ways ofcultivating the cape crop. The community expects the follow-up of this activity, so that theparticipation of the community in preserving the environment is a priority.